PENGEMBANGAN DAN OPTIMASI FORMULA GEL DAUN SELEDRI (Apium graveolens L.) BERBASIS KITOSAN-ALGINAT DENGAN METODE BOX-BEHNKEN SEBAGAI PENUMBUH RAMBUT - Angga Saputra Yasir; Nofita Nofita (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2020)
ABSTRACT Getting old and environmental factors can deteriorate to hair problems. Celery (Apium graveolens L.) is a plant that is easily found in Indonesia and has been shown to have activity to increase hair growth. One of the pharmaceutical preparations that are applied in hair growth preparations is a gel. Gels generally use synthetic polymers, but in this study a natural polymer from chitosan and alginate was used as a base. Apart from their suitable rheological properties, chitosan and alginate are also known to have benefits in hair health. The purpose of this study was to maximize the use of celery leaves as hair growth in the form of a gel dosage form based on chitosan-alginate using the Box-Behnken response surface design method. This research was started from extracting celery leaves with ethanol, phytochemical screening, and determination of total flavonoid levels, making gels, and testing the hair growth activity. The results showed that the celery extract positively contained flavonoids (47.635 ppm / 0.5%), saponins, tannins, alkaloids, and steroids. The optimal formula is the middle formula with extract content of 0.5%, the ratio of chitosan: alginate (Chi/Alg) 1:1 and 4% base concentration. The FTIR spectrum showed that gel formation was due to the charge interaction between alginate and chitosan. The activity test results showed that the Chi/Alg base had an effect on hair growth but the concentration of celery extract 0.5% on that basis had no benefit compared to the base alone because the concentration was too low. Keywords: Celery, Chitosan, Alginate, Gel, Hair